2017
DOI: 10.1103/physrevphyseducres.13.010108
|View full text |Cite
|
Sign up to set email alerts
|

Developing skills versus reinforcing concepts in physics labs: Insight from a survey of students’ beliefs about experimental physics

Abstract: Physics laboratory courses have been generally acknowledged as an important component of the undergraduate curriculum, particularly with respect to developing students' interest in, and understanding of, experimental physics. There are a number of possible learning goals for these courses including reinforcing physics concepts, developing laboratory skills, and promoting expert-like beliefs about the nature of experimental physics. However, there is little consensus among instructors and researchers interested… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 29 publications
4
56
1
Order By: Relevance
“…Red and pink represent students' responses from their own perspective for FY and BFY students, respectively, and blue and teal points represent students' predictions of what an experimental physicist might say for FY and BFY students, respectively. in the majority of the prior E-CLASS publications [23,26,29]. However, the 2-point scheme is consistent with the representations used in the reports received by instructors using E-CLASS through our centralized system [25].…”
Section: Scoring and Analysissupporting
confidence: 56%
See 1 more Smart Citation
“…Red and pink represent students' responses from their own perspective for FY and BFY students, respectively, and blue and teal points represent students' predictions of what an experimental physicist might say for FY and BFY students, respectively. in the majority of the prior E-CLASS publications [23,26,29]. However, the 2-point scheme is consistent with the representations used in the reports received by instructors using E-CLASS through our centralized system [25].…”
Section: Scoring and Analysissupporting
confidence: 56%
“…Similarly, we have measured a significant improvement in E-CLASS scores in courses that use well-established transformed curricula compared to traditional labs at the introductory level, and the increase is significantly larger for women [28]. Finally, we have shown that courses that focus more on developing lab skills outperform courses that focus more on reinforcing physics concepts, and again, the increase is significantly larger for women [29].…”
Section: Introductionmentioning
confidence: 68%
“…Another possible claim is that the lab increases student motivation, which then is reflected in improved overall course performance. Studies of both concepts-based and structured lab courses, however, have shown that student attitudes and motivation towards experimental physics decrease by the end of such courses [15,27]. Regardless of whether the learning in the lab leads to improved learning in other aspects of the course, what we have shown is that these labs are not…”
Section: Discussionmentioning
confidence: 51%
“…The researchers compared the responses of students based on the structures of the lab courses in which they were enrolled. They found that students' perceptions of experimental physics became less expertlike in courses that were more guided compared with ones with open-ended activities [15] and in ones whose primary goals included focus on developing or reinforcing physics concepts compared with ones that focused on skills [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation